PENGARUH PENGELOLAAN PROGRAM PENGAJARAN KEPALA SEKOLAH SEBAGAI DIMENSI KEPEMIMPINAN INSTRUKSIONAL TERHADAP KUALITAS PEMBELAJARAN GURU DI SEKOLAH - Aprilian, Wahyu Rizky; Umma, Sara Zakiyyatul; Avisa, Gizza Mardiana Nur; Putri, Vina Cahaya; Pratiwi, Nabila Az Zahra Dwi; Roesminingsih, Erny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of the principal’s instructional program management as a dimension of instructional leadership on the quality of teacher learning at TK Aisyiyah 05 Surabaya. The study was motivated by the important role of principals in improving learning quality through planning, supervision, evaluation, and continuous teacher development. This research employed a mixed methods approach with an explanatory sequential design, where quantitative data were strengthened by qualitative findings. Quantitative data were collected through questionnaires distributed to 28 respondents, while qualitative data were obtained through interviews and observations. Quantitative analysis used validity, reliability, normality, Spearman Rho correlation, and coefficient of determination tests. The findings revealed a positive and significant relationship between the principal’s instructional program management and the quality of teacher learning, with a correlation value of rs = 0.426 and a significance value of 0.024 < 0.05. The instructional program management variable contributed 25.7% to the quality of teacher learning. Qualitative findings showed that the principal implemented instructional program management through work meetings, curriculum coordination, academic supervision, learning evaluation, and regular teacher training. Therefore, the principal’s instructional program management as a dimension of instructional leadership influences the improvement of teacher learning quality at school.